2021
DOI: 10.1038/s41398-021-01217-w
|View full text |Cite
|
Sign up to set email alerts
|

Trazodone effects on developing brain

Abstract: Trazodone (TRZ) is a commonly prescribed antidepressant with significant off-label use for insomnia. A recent drug screening revealed that TRZ interferes with sterol biosynthesis, causing elevated levels of sterol precursor 7-dehydrocholesterol (7-DHC). Recognizing the well-documented, disruptive effect of 7-DHC on brain development, we designed a study to analyze TRZ effects during pregnancy. Utilizing an in vivo model and human biomaterial, our studies were designed to also account for drug interactions with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Three drugs, aripiprazole, haloperidol and trazodone were associated with increased circulating 7DHC and 8DHC levels, while five other drugs, clozapine, escitalopram/citalopram, lamotrigine, olanzapine, and risperidone, were not. In separate biobank sample studies, we found that 7-DHC levels were also higher in patients with detectable levels of CAR and TRZ in their blood ( 111 , 113 ). While these findings are only minimally informative about the sterol synthesis events in the brain (as brain and body sterol synthesis are distinct and separated by the blood-brain barrier), they lead us to the conclusion that drugs can possess sterol-inhibiting function both in the brain and the body.…”
Section: Interaction Of Genetic and Chemical Inhibitionmentioning
confidence: 82%
See 2 more Smart Citations
“…Three drugs, aripiprazole, haloperidol and trazodone were associated with increased circulating 7DHC and 8DHC levels, while five other drugs, clozapine, escitalopram/citalopram, lamotrigine, olanzapine, and risperidone, were not. In separate biobank sample studies, we found that 7-DHC levels were also higher in patients with detectable levels of CAR and TRZ in their blood ( 111 , 113 ). While these findings are only minimally informative about the sterol synthesis events in the brain (as brain and body sterol synthesis are distinct and separated by the blood-brain barrier), they lead us to the conclusion that drugs can possess sterol-inhibiting function both in the brain and the body.…”
Section: Interaction Of Genetic and Chemical Inhibitionmentioning
confidence: 82%
“…Hall et al made a critical observation of cholesterol biosynthesis interference by medications, noting that some patients who used aripiprazole and trazodone were misidentified as SLOS patients based on their blood 7-DHC levels ( 109 ). Following up on these observations, over the last seven years we validated that haloperidol, aripiprazole, trazodone, and cariprazine are all strong inhibitors of sterol biosynthesis, and that they have profound biochemical effects on the fetal brain in rodent models ( 110 113 ). It is also important to point out that the above-mentioned compounds appears to inhibit directly the DHCR7 enzyme, as it occurs in the cell systems without the receptors targeted by the drugs.…”
Section: Chemical Modulation Of Cholesterol Biosynthesismentioning
confidence: 83%
See 1 more Smart Citation
“…Next, we investigated whether the differences in brain sterol concentrations could be explained by medication use, based on recent reports of inhibition of key cholesterol synthesis enzymes by psychotropic medications [ 17 – 19 , 35 , 36 ]. We considered data from both medication use history and toxicology reports, and identified morphine, ethanol, trazodone, escitalopram, alprazolam, diphenhydramine, hydrocodone, aspirin, atropine, insulin, and lisinopril as the only medications used by or found in >2 subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in brain cholesterol concentrations have long been associated with suicide and depression. More recently, four psychotropic medications, aripiprazole, cariprazine, haloperidol, and trazodone have been shown to be inhibitors of 7-dehydrocholesterol reductase, leading to increased 7DHC and reduced desmosterol levels in cell culture, rodents (including in utero models), human dermal fibroblasts, and human blood [ 17 , 19 , 20 , 35 , 36 , 38 ]. In these models, the magnitude of 7-DHC elevation was comparable to levels seen in Smith-Lemli-Opitz syndrome, a severe congenital syndrome caused by mutations in the DHCR7 gene encoding 7-dehydrocholesterol reductase.…”
Section: Resultsmentioning
confidence: 99%